A Dynamic Panel Analysis of Human Development and Environmental Sustainability in Indonesia - Ariyan Bajrayuda; Djoni Hartono (Economics Development Analysis Journal, 2026)
As decentralized emerging economies navigate the complex trade-offs between rapid industrialization and ecological preservation, understanding the nuanced drivers of environmental sustainability becomes critically imperative. This study investigates the dynamic interplay between human development and environmental quality across 34 Indonesian provinces from 2013 to 2020. Recognizing that regional ecological trajectories are highly path-dependent and that traditional static panel models frequently yield biased estimates, we employ a System Generalized Method of Moments (GMM) approach. This methodological framework rigorously addresses the inherent endogeneity and reverse causality between macroeconomic expansion and environmental outcomes. The model incorporates Foreign Direct Investment (FDI), physical capital, economic growth, and population as control variables, all of which exhibit negative coefficients, suggesting that current macroeconomic expansion and demographic pressures pose significant challenges to regional environmental quality. Despite these pressures, the research novelty reveals that human development dimensions particularly education and welfare—act as critical countervailing forces. Our findings confirm that while industrial and population scaling currently degrade the environment, qualitative improvements in human capital can catalyze a transition toward green growth. Policy implications suggest that Indonesia must shift from a 'grow first, clean up later' strategy toward selective FDI screening and 'green-weighted' development metrics to decouple economic progress from ecological decline.